Anterior mediastinal teratoma mimicking tuberculosis: A diagnostic challenge in a high tuberculosis-burden country (Indian Journal of Case Reports, 2026)
Mature teratomas are uncommon benign germ cell tumors that can occur in adults, most frequently within the anterior mediastinum. We describe the case of a 45-year-old woman presenting to the respiratory medicine outpatient clinic with a persistent dry cough, left-sided chest pain, and occasional mild hemoptysis for 6–7 months. Initial chest radiograph revealed a left mediastinal opacity with a hilum overlay sign. Computed tomography (CT) suggested a differential of thymolipoma versus germ cell tumor, with histopathological confirmation recommended. CT-guided biopsy established the diagnosis of a mature teratoma, and the patient was subsequently referred for surgical excision. Although benign, mediastinal teratomas may mimic serious pulmonary conditions and cause alarming symptoms such as hemoptysis. Correlating clinical, radiological, and histopathological findings is essential for accurate diagnosis and timely management.